Three diagnostic psychiatric subgroups in comparison to self-stigma, quality of life, disorder severity and coping management cross-sectional outpatient study - Holubova, Michaela; Prasko, Jan; Ociskova, Marie; Vanek, Jakub; Slepecky, Milos; Zatkova, Marta; Latalova, Klara; Kolek, Antonín (Neuro endocrinology letters, 2018)
BACKGROUND: Much attention has been paid to psychological factors influencing characteristics, severity, and course of mental disorders. The objective of our investigation was to examine the interrelations among quality of life (QoL), self-stigma, and coping strategies, demographics and severity of the disorder in neurotic spectrum disorders, schizophrenia, and depressive spectrum disorders. METHODS: A total of 343 clinically stable Czech outpatients with different mental disorders (153 with neurotic spectrum disorders; 81 with depression, and 109 with schizophrenia spectrum disorders) were included. The patients were examined by their outpatient psychiatrists during regular psychiatric checkup and completed a sociodemographic questionnaire, the Quality of Life Satisfaction and the Enjoyment Questionnaire (Q-LES-Q), the Internalized Stigma of Mental Illness Scale (ISMI), the Stress Coping Style Questionnaire (SVF-78), and the Clinical Global Impression scale (CGI). RESULTS: The study demonstrates that the self-stigma and coping strategies are significant factors linked to the QoL in all diagnostic groups of patients. Patients with schizophrenia spectrum disorders had lower scores in QoL compared to the other two groups. The patients with depression or neurotic spectrum disorders had a lesser degree of self-stigma than the patients with schizophrenia spectrum disorders. The severity of the illness significantly correlated with the QoL, self-stigma, and coping strategies. CONCLUSIONS: The investigation confirmed the connection between the quality of life, self-stigma, coping strategies, and the severity of the illness, in outpatients with schizophrenia spectrum disorders, depressive, and neurotic spectrum disorders. A further longitudinal study would be useful to determine the causative relationships of these variables.
Keywords: dospělí; Female; Social Stigma; Adaptation, Psychological; Quality of Life; Adult; sebepojetí; ženské pohlaví; duševní poruchy; průřezové studie; úzkostné poruchy; Schizophrenic Psychology; Self Concept; kvalita života; lidé; psychotické poruchy; společenské stigma; schizofrenie; stupeň závažnosti nemoci; neurotické poruchy; adaptace psychologická; Anxiety Disorders; Cross-Sectional Studies; Male; depresivní poruchy; Psychotic Disorders; Outpatients; Schizophrenia; pacienti ambulantní; Depressive Disorder; Mental Disorders; lidé středního věku; mužské pohlaví; Severity of Illness Index; schizofrenie (psychologie); Middle Aged; Neurotic Disorders; Humans